Relationship of Stromal Tumor Infiltrating Lymphocytes (STILs) with Grading Histopathology in Penis Squamous Cell Carcinoma - Sihotang, Marisi Cintya Debby; Intan, T. Kemala; Alferraly, T. Ibnu; Betty, Betty; Soekimin, Soekimin; Delyuzar, Delyuzar (Majalah Patologi Indonesia, 2024)
ABSTRACT Background:Penile squamous cell carcinoma is the most common penile malignance found in the world. Assessment of stromal tumor infiltrating lymphocytes (STILs) associated with grading against penile squamous cell carcinoma can provide a potential prognostic picture and help determine the action. Method:Cross-sectional analytical study with 32 samples of histopathological preparations diagnosed as penile squamous cell carcinoma at H. Adam Malik Hospital Medan. The assessment of stromal TILs was carried out by assessing the number of lymphocyte inflammatory cells in the peritumoral stroma and then determined the assessment score, zero score no lymphocytes (minimum), score one found 0-10% lymphocytes (moderately), score two found 20-40% lymphocytes (massive) , score three found 50-90% lymphocytes. Grading assessments are categorized into grade I (well differentiated), grade II (moderately differentiated), and grade III (poorly differentiated). Result:The most grading found was grade II (43.8%) and the most STILs found were score three (50.0%). There is a significant relationship between grading and STILs in penile squamous cell carcinoma (p value=0.0001) i.e. the higher the STILs score , the lower the tumor grade. Conclusion:There is a relationship between STILs and histopathological grading in Penile Squamous Cell Carcinoma so that it can be used as an indikasi prognosis in patients with penile squamous cell carcinoma.